Short-term dynamics of Quercus ilex advance regeneration in a Pinus nigra plantation after the creation of small canopy gaps - Garcia-Barreda, S.; Reyna, S. (FOREST SYSTEMS, 2013)
Aim of the study: The aim of the research is to analyse the role of Quercus ilex advance regeneration in the stand regeneration of pine plantations after small-sized canopy openings, and to assess the influence of the forest stand and the canopy opening. The performance of the advance regeneration under the pine plantation is also examined. Area of study: A Pinus nigra plantation in dry Continental Mediterranean climate in eastern Spain. Material and methods: The tree regeneration of ten canopy openings of 0.17-0.43 ha was monitored during five years after treatment. It was also sampled in 0.12 ha-plots in the non-treated pine plantation surrounding the openings. Main results: An important increase in the height of Q. ilex regeneration was observed in the openings, unlike what was found in the intact pine plantation. In the pine plantation, stand density showed a moderate positive influence on the density of Q. ilex regeneration, whereas in the canopy gaps Q. ilex height was negatively influenced by stand density before the opening. Research highlights: The canopy opening triggered a response in Q. ilex advance regeneration, although height growth rates seemed to reduce over time. The results support the view that promoting Q. ilex in pine plantations may require different management strategies depending on the characteristics of the pine overstorey and on the density and size of the advance regeneration.
The following values have no corresponding Zotero field: pub-location: CTRA CORUNA KM 7 5, MADRID, 28040, SPAIN publisher: INST NACIONAL INVESTIGACION TECHNOLOGIA AGRARIA ALIMENTARIA
Keywords: group selection cutting; mediterranean forest; seedling resprout; stand initiation; truffle